2018
DOI: 10.22442/jlumhs.181730570
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid act as a Non - Invasive Marker for Diagnosis of Liver Fibrosis in the Patients of Chronic Hepatitis C

Abstract: 350 samples, 100 normal samples were recruited as control group and 250 diagnosed cases of chronic hepatitis C patients were recruited as case study group. Serum Hyaluronic acid was significantly (P<0.001) elevated in patients (195.77 ±6.67) compared to controls (110.2 ±0.79) irrespective of gender involvement. CONCLUSION: The current findings showed significant involvement of HA in early prognosis of liver fibrosis and cirrhosis among chronic HCV patients that would probably useful to reduce repetitive liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study conducted by Akram et al concluded in contrast to the control group, HA levels were found to be two times higher among people infected with hepatitis C. 16 Murawaki et al have reported statistically significant variations in HA levels in chronic hepatitis C patients at different stages of hepatic fibrosis. 17 Tao et al also reported the higher levels of serum HA and LN among cases and controls of cirrhotic patients as the stages of fibrosis advances.…”
mentioning
confidence: 95%
“…A study conducted by Akram et al concluded in contrast to the control group, HA levels were found to be two times higher among people infected with hepatitis C. 16 Murawaki et al have reported statistically significant variations in HA levels in chronic hepatitis C patients at different stages of hepatic fibrosis. 17 Tao et al also reported the higher levels of serum HA and LN among cases and controls of cirrhotic patients as the stages of fibrosis advances.…”
mentioning
confidence: 95%